Effect of a physical activity and behaviour maintenance programme on functional mobility decline in older adults: the REACT (Retirement in Action) randomised controlled trial. (April 2022) - Stathi, Afroditi; Greaves, Colin J; Thompson, Janice L; Withall, Janet; Ladlow, Peter; Taylor, Gordon; Medina-Lara, Antonieta; Snowsill, Tristan; Gray, Selena; Green, Colin; Johansen-Berg, Heidi; Sexton, Claire E; et al.
Summary: Background: Mobility limitations in old age can greatly reduce quality of life, generate substantial health and social care costs, and increase mortality. Through the Retirement in Action (REACT) trial, we aimed to establish whether a community-based active ageing intervention could prevent decline in lower limb physical functioning in older adults already at increased risk of mobility limitation. Methods: In this pragmatic, multicentre, two-arm, single-blind, parallel-group, randomised, controlled trial, we recruited older adults (aged 65 years or older and who are not in full-time employment) with reduced lower limb physical functioning (Short Physical Performance Battery [SPPB] score 4–9) from 35 primary care practices across three sites (Bristol and Bath; Birmingham; and Devon) in England. Participants were randomly assigned to receive brief advice (three healthy ageing education sessions) or a 12-month, group-based, multimodal physical activity (64 1-h exercise sessions) and behavioural maintenance (21 45-min sessions) programme delivered by charity and community or leisure centre staff in local communities. Randomisation was stratified by site and adopted a minimisation approach to balance groups by age, sex, and SPPB score, using a centralised, online, randomisation algorithm. Researchers involved in data collection and analysis were masked but participants were not because of the nature of the intervention. The primary outcome was change in SPPB score at 24 months, analysed by intention to treat. This trial is registered with ISRCTN, ISRCTN45627165. Findings: Between June 20, 2016, and Oct 30, 2017, 777 participants (mean age 77·6 [SD 6·8] years; 66% female; mean SPPB score 7·37 [1·56]) were randomly assigned to the intervention (n=410) and control (n=367) groups. Primary outcome data at 24 months were provided by 628 (81%) participants (294 in the control group and 334 in the intervention group). At the 24-month follow-up, the SPPB score (adjusted for baseline SPPB score, age, sex, study site, and exercise group) was significantly greater in the intervention group (mean 8·08 [SD 2·87]) than in the control group (mean 7·59 [2·61]), with an adjusted mean difference of 0·49 (95% CI 0·06–0·92; p=0·014), which is just below our predefined clinically meaningful difference of 0·50. One adverse event was related to the intervention; the most common unrelated adverse events were heart conditions, strokes, and falls. Interpretation: For older adults at risk of mobility limitations, the REACT intervention showed that a 12-month physical activity and behavioural maintenance programme could help prevent decline in physical function over a 24-month period. Funding: National Institute for Health Research Public Health Research Programme (13/164/51). Graphical abstract: Image, graphical abstract